2009
DOI: 10.1111/j.1365-3121.2009.00864.x
|View full text |Cite
|
Sign up to set email alerts
|

Petroleum surface oil seeps from a Palaeoproterozoic petrified giant oilfield

Abstract: Early Palaeoproterozoic rocks from the Onega Basin in Russian Fennoscandia contain evidence for substantial accumulation and preservation of organic matter (up to 75 wt% total organic carbon) with an estimated original petroleum potential comparable to a modern supergiant oilfield. The basin contains a uniquely preserved petrified oilfield including evidence of oil traps and oil migration pathways. Here, we report the discovery of the surface expression of a migration pathway, along which petroleum was flowing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
37
0
3

Year Published

2010
2010
2012
2012

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 16 publications
1
37
0
3
Order By: Relevance
“…Several intervals are pervasively impregnated with pyrobitumen that results in obliteration of sedimentary layering, and in places massive appearance of the host sedimentary rock (Fig.2). Numerous veins consisting largely of pyrobitumen or containing also quartz and carbonate can be observed throughout the Zaonega Formation as well as in overlying sedimentary and volcanic rocks (Melezhik et al, 2009;Melezhik et al, 1999). Pyrobitumen-rich intervals that are in places rich in silicates (Melezhik et al, 2004), are found in the contact zones of magmatic bodies, but also occur as layers within sedimentary successions.…”
Section: Geologic Descriptionmentioning
confidence: 98%
See 1 more Smart Citation
“…Several intervals are pervasively impregnated with pyrobitumen that results in obliteration of sedimentary layering, and in places massive appearance of the host sedimentary rock (Fig.2). Numerous veins consisting largely of pyrobitumen or containing also quartz and carbonate can be observed throughout the Zaonega Formation as well as in overlying sedimentary and volcanic rocks (Melezhik et al, 2009;Melezhik et al, 1999). Pyrobitumen-rich intervals that are in places rich in silicates (Melezhik et al, 2004), are found in the contact zones of magmatic bodies, but also occur as layers within sedimentary successions.…”
Section: Geologic Descriptionmentioning
confidence: 98%
“…The Paleoproterozoic Zaonega succession of siliciclastic, carbonate and sedimentary rocks, and mafic tuff, interlayered and intersected by mafic lavas and sills (Galdobina, 1987), is exceptionally rich in organic carbon (Fillipov, 1994), and represents one of the earliest geological manifestations of significant petroleum generation in Earth history (Melezhik et al, 2009;Melezhik et al, 1999). These organic-rich rocks have often been referred to as shungite (after Shunga village in Karelia), which in the literature appears as a general term for organic carbonrich rocks from the Paleoproterozoic Onega Basin (Buseck et al, 1997;Fillipov, 1994;Kovalevski et al, 2001), although many authors (Kovalevski, 1994;Melezhik et al, 1999) describe shungite as a type of CM found in these rocks following the original terminology of Inostranzev (1879).…”
Section: Geologic Descriptionmentioning
confidence: 99%
“…However, the presence of organic matter within the stratigraphic column that records the Shunga Event on the Fennoscandian Shield is highly complex and includes sediments that might have escaped substantial mobilisation of organic matter, different generations of migrated bitumen, cross-cutting veins filled with bitumen, and redeposited organic matter (e.g. Melezhik et al 2009). Considering the different rock types and different appearance of organic matter within the stratigraphy, the range in d 13 C org would be consistent with a common biological source but would also suggest modifications of the d 13 C org signature during postdepositional thermal alteration, migration and redeposition.…”
mentioning
confidence: 99%
“…Considering the substantial amount of organic matter deposited on the Fennoscandian Shield (Melezhik et al 2009), let alone worldwide during the time of the Shunga Event, places some as yet not quantified constraints on the chemical composition of the ocean. Most critical is the aspect of nutrient availability.…”
mentioning
confidence: 99%
“…The most remarkable accumulation of organic-matter-rich sediments and generation of petroleum in the Precambrian took place at around 2000 Ma ago in the aftermath of the Lomagundi-Jatuli Event (Melezhik et al, 2009). This is known as the Shunga Event.…”
Section: Supergiant Petroleum Depositsmentioning
confidence: 99%